Bi‐Functional Mechanism in Degradation of Toxic Water Pollutants by Catalytic Amorphous Metals. Issue 2 (19th June 2015) - Das, Santanu; Garrison, Seth; Mukherjee, Sundeep
Abstract : The authors report on the high catalytic activity and bi‐functional catalysis mechanism of amorphous metals in degrading AZO Dye, a toxic water pollutant and carcinogen. Aluminum‐based metallic glass was found to completely degrade AZO dye at room temperature without any toxic by‐products. The high catalytic activity originates from the simultaneous ionization of the transition metals, which act as electron donors for rapid degradation of AZO dye in an aqueous medium. The dye degradation rate and catalytic activity were characterized via UV–VIS absorption spectroscopy. The rate of dye degradation was significantly faster compared to state‐of‐the‐art zero valent iron. The dye degradation mechanism was studied using Raman and IR spectroscopy combined with X‐ray photoelectron spectroscopy. Abstract : AZO dye is a toxic water pollutant and carcinogen used widely as a coloring agent in textile industries. Efficient catalytic degradation of AZO dye by aluminum based metallic glass particles is presented in this report. The high catalytic activity originates from the simultaneous ionization of the transition metals in the alloy, which help in charge transfer to the NN bonds in AZO dye, resulting in rapid degradation of AZO dye in an aqueous medium.